Simulator Development - Annual Report Year 3 - Werner Streitberger; Torsten Eymann; Floriano Zini; Björn Schnizler; Hong Tuan Kiet Vo (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2007)
This document describes the progress of the simulator development with in the third year of the CATNETS project. The refinement of the simulator as well as a detailed guide to conducting simulations is presented.
urn:nbn:de:bvb:703-opus-3709
Keywords: 004; Grid Computing